2019
DOI: 10.1186/s12889-019-7770-5
|View full text |Cite
|
Sign up to set email alerts
|

Companion dog acquisition and mental well-being: a community-based three-arm controlled study

Abstract: BackgroundDog ownership is suggested to improve mental well-being, although empirical evidence among community dog owners is limited. This study examined changes in human mental well-being following dog acquisition, including four measures: loneliness, positive and negative affect, and psychological distress.MethodsWe conducted an eight-month controlled study involving three groups (n = 71): 17 acquired a dog within 1 month of baseline (dog acquisition); 29 delayed dog acquisition until study completion (lagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 78 publications
(88 reference statements)
3
55
1
Order By: Relevance
“…Furthermore, qualitative insights from a Must Love Dogs intervention programme for older Australians living alone suggest that interactions with dogs can increase positive affect in a group setting (Papotto & Oliva, 2019). However, Powell et al (2019) found that when the level of education was adjusted for in their analyses, the effects of dog acquisition on loneliness were nullified, and a systematic review by Gilbey and Tani (2015) has cast doubt on the convincingness of the extant quantitative evidence that companion animals alleviate loneliness, expressing a need for more research to be conducted under 'controlled' conditions with a consideration for the time participants actually spend with their animal. One such study, a randomised controlled trial comparing a mindfulness intervention group, a dog interaction group and a control group, was able to demonstrate that similar reductions in state anxiety and depression levels could be gained from both the mindfulness intervention and dog interaction groups, as compared to the control group (Shearer et al, 2016).…”
mentioning
confidence: 99%
“…Furthermore, qualitative insights from a Must Love Dogs intervention programme for older Australians living alone suggest that interactions with dogs can increase positive affect in a group setting (Papotto & Oliva, 2019). However, Powell et al (2019) found that when the level of education was adjusted for in their analyses, the effects of dog acquisition on loneliness were nullified, and a systematic review by Gilbey and Tani (2015) has cast doubt on the convincingness of the extant quantitative evidence that companion animals alleviate loneliness, expressing a need for more research to be conducted under 'controlled' conditions with a consideration for the time participants actually spend with their animal. One such study, a randomised controlled trial comparing a mindfulness intervention group, a dog interaction group and a control group, was able to demonstrate that similar reductions in state anxiety and depression levels could be gained from both the mindfulness intervention and dog interaction groups, as compared to the control group (Shearer et al, 2016).…”
mentioning
confidence: 99%
“…In our cross-sectional study, we did not assess when or for what reason the pet was acquired or how attachment to pet changed in the course of symptom development and thus, we are not able to test this hypothesis. However, studies looking at the potential benefits of recent dog adoption (in contrast to dog ownership) [70] showed that dog adoption was quite consistently associated with positive psychological outcomes such as reduced loneliness in healthy adults as well as patients with PTSD [25] and Major Depressive Disorder [26]. Nevertheless, more differentiated prospective studies are needed to investigate whether a stronger attachment to pets develops due to a higher psychopathological symptom burden or whether a stronger attachment to pets constitutes a risk factor for the development of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the mental health benefits of owning a companion animal, such as a dog or a cat, have been shown by several scientific studies (Serpell, 1991;Beetz et al, 2012;Powell et al, 2019). The majority of studies indicate that interactions with animals may help with depression, anxiety, and stress, in particular under stress-prone conditions (Beetz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies indicate that interactions with animals may help with depression, anxiety, and stress, in particular under stress-prone conditions (Beetz et al, 2012). On the one hand, companion animals provide companionship, improve mood, and may ease loneliness; human-animal interactions may even improve peer-to-peer social relationships, as well as enhance feelings of respect, trust, and empathy between people (Powell et al, 2018;Beetz et al, 2012;Powell et al, 2019). On the other hand, it has also been shown that stress and poor well-being of owners negatively affect the stress and well-being of their companion animals (Buttner et al, 2015;Sumegi et al, 2014;Ryan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%